Current Direct Neutrino Mass Experiments. (13th February 2013) - Drexlin, G.; Hannen, V.; Mertens, S.; Weinheimer, C.
Abstract : In this contribution, we review the status and perspectives of direct neutrino mass experiments, which investigate the kinematics of β -decays of specific isotopes ( 3 H, 187 Re, 163 Ho) to derive model-independent information on the averaged electron (anti)neutrino mass. After discussing the kinematics of β -decay and the determination of the neutrino mass, we give a brief overview of past neutrino mass measurements (SN1987a-ToF studies, Mainz and Troitsk experiments for 3 H, cryobolometers for 187 Re). We then describe the Karlsruhe Tritium Neutrino (KATRIN) experiment currently under construction at Karlsruhe Institute of Technology, which will use the MAC-E-Filter principle to push the sensitivity down to a value of 200 meV (90% C.L.). To do so, many technological challenges have to be solved related to source intensity and stability, as well as precision energy analysis and low background rate close to the kinematic endpoint of tritium β -decay at 18.6 keV. We then review new approaches such as the MARE, ECHO, and Project8 experiments, which offer the promise to perform an independent measurement of the neutrino mass in the sub-eV region. Altogether, the novel methods developed in direct neutrino mass experiments will provide vital information on the absolute mass scale of neutrinos.